2020
DOI: 10.5194/mr-1-285-2020
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to identify and suppress crosstalk signals in double electron–electron resonance (DEER) experiments with gadolinium<sup>III</sup> and nitroxide spin-labeled compounds

Abstract: Abstract. Double electron–electron resonance (DEER) spectroscopy applied to orthogonally spin-labeled biomolecular complexes simplifies the assignment of intra- and intermolecular distances, thereby increasing the information content per sample. In fact, various spin labels can be addressed independently in DEER experiments due to spectroscopically nonoverlapping central transitions, distinct relaxation times, and/or transition moments; hence, they are referred to as spectroscopically orthogonal. Molecular com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The amplitude of the Gd 3+ –Gd 3+ crosstalk signal is decreased (DEERNet suggested a total absence; see Figure b vs d). This might be due to the presence of additional Gd 3+ (BtuF) in the sample, which reduces the relative ratio between different spin pairs . The Gd 3+ –NO (BtuF–T-CNCbl) PELDOR revealed a somewhat longer distance (Figure c, also shown in Figure e), and a partial contribution (crosstalk) from it might account for the broadening of Gd 3+ –trityl distances.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The amplitude of the Gd 3+ –Gd 3+ crosstalk signal is decreased (DEERNet suggested a total absence; see Figure b vs d). This might be due to the presence of additional Gd 3+ (BtuF) in the sample, which reduces the relative ratio between different spin pairs . The Gd 3+ –NO (BtuF–T-CNCbl) PELDOR revealed a somewhat longer distance (Figure c, also shown in Figure e), and a partial contribution (crosstalk) from it might account for the broadening of Gd 3+ –trityl distances.…”
Section: Resultsmentioning
confidence: 95%
“…For the Gd 3+ –NO PELDOR, it was shown that an additional crosstalk signal corresponding to the Gd 3+ –Gd 3+ distance could appear due to the (suboptimal) coexcitation of underlying Gd 3+ spins by the NO pump pulse. , Their nutation experiments showed that, even at ∼290 MHz lower from the spectral maximum, pulses mostly excited the M S = −1/2 to M S = +1/2 transition. Pumping trityl could enhance this crosstalk signal due to the smaller frequency offset (Figure d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 (ESI†) for the DEER setups and Table S3 (ESI†) for the experimental parameters) on a dinitroxide ruler (NO–NO ruler; see Materials and Methods) with 2.0 nm interspin distance that is soluble in aqueous solvents. 54 The MS-3 resonator required an incident power of 45 W at the resonator to perform the experiment. In contrast, the microhelix required only 43 mW of incident power.…”
Section: Resultsmentioning
confidence: 99%
“…The structural formula is presented in Fig. 9(a), and the synthesis is described in Teucher et al 54 The ruler consists of two nitroxides that are held by a stiff rod-like spacer at a distance of 2.0 nm. 64 A stock solution of the NO–NO ruler was prepared in D 2 O using 50% v/v deuterated glycerol to ensure a glass-like freezing at a 1.4 mM final molecule concentration.…”
Section: Methodsmentioning
confidence: 99%